Divergent trajectories to structural diversity impact patient survival in high grade serous ovarian cancer - Ailith Ewing; Alison Meynert; Ryan Silk; Stuart Aitken; Devin P. Bendixsen; Michael Churchman; Stuart L. Brown; Alhafidz Hamdan; Joanne Mattocks; Graeme R. Grimes; Tracy Ballinger; Robert L. Hollis; et al. (Nature Communications)
Abstract Deciphering the structural variation across tumour genomes is crucial to determine the events driving tumour progression and better understand tumour adaptation and evolution. High grade serous ovarian cancer (HGSOC) is an exemplar tumour type showing extreme, but poorly characterised structural diversity. Here, we comprehensively describe the mutational landscape driving HGSOC, exploiting a large (N = 324), deeply whole genome sequenced dataset. We reveal two divergent evolutionary trajectories, affecting patient survival and involving differing genomic environments. One involves homologous recombination repair deficiency (HRD) while the other is dominated by whole genome duplication (WGD) with frequent chromothripsis, breakage-fusion-bridges and extra-chromosomal DNA. These trajectories contribute to structural variation hotspots, containing candidate driver genes with significantly altered expression. While structural variation predominantly drives tumorigenesis, we find high mtDNA mutation loads associated with shorter patient survival. We show that a combination of mutations in the mitochondrial and nuclear genomes impact prognosis, suggesting strategies for patient stratification.